DIGITAL NATIONALISM OLEH NETIZEN INDONESIA (Digital Discourse Analysis Dalam Fenomena SEAblings vs K-netz Pada Media Sosial X) - Nur Fitri Sofyan Putri; Dian Hutami Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
through tweets of comments on social media X (Twitter) by utilizing features of likes, comments, reposts, and hashtags. One interesting phenomenon is the SEAblings (South-East Asian netizens) conflict with K-netz (Korean netizens) that features the dynamics of digital nationalism, regional solidarity, and resistance to stereotypes in digital public spaces. This research aims to find out the digital nationalism of Indonesian netizens and digital discourse analysis about the phenomenon of SEAblings vs. K-netz on social media X. The research object is the phenomenon of SEAblings vs. K-Netz on social media X (Twitter), with a focus on digital nationalism practices by Indonesian netizens. The data is collected through media text, documentation, and literature studies, and then analyzed by considering four aspects: text (the element of semiotics), context (the meaning behind the text), action and interaction (effect on others), and ideology and power (the relationship of certain powers). The results showed that the phenomenon of SEAblings vs. K-netz shaped the digital nationalism practice of Indonesian netizens through the formation of solidarity, collective use of language, and cross-cultural interaction in the X social media space, where the tweets of comments did not only display conflict, they did not only. but also efforts to build perceptions and ease tensions through digital literacy and communication strategies. This study concluded that digital nationalism of Indonesian netizens came as a form of solidarity of identity built through interaction, language, and digital communication in X's social media public space.